Unemployment in Nigeria: Can need for power improve the scourge? - Owenvbiugie, Robinson Osarumwense; Egbri, Jane Nwakego (International Business Education Journal, 2020)
The study described a Nigerian Government program called the Need for Power (N-Power) in reducing the unemployment rate. Questionnaires were distributed to 115 respondents sampled using an accidental sampling technique, and a descriptive analysis was conducted to determine the influence of N-Power in generating employment opportunities. The reliability of 0.81 was obtained with the use of the Cronbach alpha formula. From the result, N-Power Volunteer Corps, N-Power Builds, N-Power Creative, and N-Power Knowledge generated employment to a high extent. It was also concluded that males’ employment opportunities generated by N-Power did not significantly differ from females’. Consequently, this study recommended that the Government listen to the beneficiaries’ complaints to declare their actual income voluntarily, increase the monthly stipend of N10,000 per month to encourage more youths to participate in the program, and link training to job and labour market opportunities.